2020
DOI: 10.1007/s41775-020-00097-z
|View full text |Cite
|
Sign up to set email alerts
|

Goods and Services Tax efficiency across Indian States: panel stochastic frontier analysis

Abstract: In public finance, estimation of tax potential of a government -either federal or provincial -has immense importance to understand future streams of tax revenue. Tax potential depends on tax capacity and tax effort (TE) and therefore joint estimation of both the functions is desirable. There are several frameworks to estimate tax capacity and tax efficiency (tax effort); in the present paper time variant truncated panel Stochastic Frontier Approach (SFA) is adopted to estimate the functions jointly for the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…After filtering out companies with missing information, the final data set consists of 43 companies listed in Bursa Malaysia during the period from 2002 to 2011. In order to analyse the data, the study applies the Stochastic Frontier Analysis (SFA) (Mukherjee, 2020). SFA is the estimation tool to estimate the frontier function and to measure the production efficiency of the firms.…”
Section: Methodsmentioning
confidence: 99%
“…After filtering out companies with missing information, the final data set consists of 43 companies listed in Bursa Malaysia during the period from 2002 to 2011. In order to analyse the data, the study applies the Stochastic Frontier Analysis (SFA) (Mukherjee, 2020). SFA is the estimation tool to estimate the frontier function and to measure the production efficiency of the firms.…”
Section: Methodsmentioning
confidence: 99%
“…The pre-designed and pre-tested questionnaire is used for the collection of primary data (refer to Appendix Table A1). We tested the pre-designed questionnaire on 35 exporters where we asked their opinion on drawback rates (Thowseaf & Millath, 2016;Revathi et al, 2019), long-run performance (Deshmukh, 2022), harmonization (Tiwari & Singh, 2018;Mukherjee, 2020), logistics cost (Deswal, 2019;Ojha & Vrat, 2018), IGST (Kumar, 2018), filing process, technical complications (Rao, 2019), transaction cost (Khoja & Khan, 2020), etc. In the later stage (main data collection), we added a few more variables based on the suggestions from motor and pump exporters and an extensive literature review.…”
Section: Data Sourcementioning
confidence: 99%
“…In the words of Mukherjee [12] viewed that the triumph of GST, in terms of compliance and mustering of revenue, is dependent on simplified tax administration process and incentivising transactions with tax invoices. In another study, Mukherjee [13] concluded that while the removal of GST compensation cess (GSTCC) will benefit some states, others might not be that beneficial. If the GST compensation is terminated in 2022 then the government needs an appropriate framework for strengthening various aspects of GST.…”
Section: Impact Of Gst On Tax Revenuementioning
confidence: 99%